Ethical Issues with Using Internet of Things Devices in Citizen Science Research: A Scoping Review - Scheibner, James; Jobin, Anna; Vayena, Effy (Frontiers in Environmental Science, 2021)
Digital innovation is ever more present and increasingly integrated into citizen science research. However, smartphones and other connected devices come with specific features and characteristics and, in consequence, raise particular ethical issues. This article addresses this important intersection of citizen science and the Internet of Things by focusing on how such ethical issues are communicated in scholarly literature. We present a scoping review of published scientific studies or case studies of scientific studies that utilise both citizen scientists and Internet of Things devices. Specifically, we selected studies where the authors had included at least a short discussion of the ethical issues encountered during the research process. We analysed the full text of relevant articles inductively and deductively and discovered three main categories of ethical issues being communicated: autonomy and data privacy, data quality, and intellectual property. Based on these categories, our review offers an overview of the legal and social innovation implications raised. We also provide recommendations for researchers who wish to innovatively integrate citizen scientists and Internet of Things devices into their research based on the strategies researchers took to resolve these ethical issues.